Memory B-cell derived donor-specific antibodies do not predict outcome in sensitized kidney transplant recipients: a retrospective single-center study - Altulea, Dania; van den Born, Joost C.; Diepstra, Arjan; Bungener, Laura; Terpstra, Dagmar; Hepkema, Bouke G.; Lammerts, Rosa; Heeringa, Peter; Heidt, Sebastiaan; Otten, Henny; Reteig, Leon; Karahan, Gonca E.; et al. (Frontiers in Immunology, 2024)
Repeated exposure to sensitizing events can activate HLA-specific memory B cells, leading to the production of donor-specific memory B cell antibodies (DSAm) that pose a risk for antibodymediated rejection (ABMR) in kidney transplant recipients (KTRs). This single-center retrospective study aimed to identify DSAm and assess their association with outcomes in a cohort of KTRs with pretransplant serum donor-specific antibodies (DSA). We polyclonally activated pretransplant peripheral blood mononuclear cells (PBMCs) from 60 KTRs in vitro, isolated and quantified IgG from the culture supernatant using ELISA, and analyzed the HLA antibodies of eluates with single antigen bead (SAB) assays, comparing them to the donor HLA typing for potential DSAm. Biopsies from 41 KTRs were evaluated for rejection based on BANFF 2019 criteria. At transplantation, a total of 37 DSAm were detected in 26 of 60 patients (43%), of which 13 (35%) were found to be undetectable in serum. No significant association was found between pretransplant DSAm and ABMR (P=0.53). Similar results were observed in a Kaplan-Meier analysis for ABMR within the first year posttransplant (P=0.29). Additionally, MFI levels of DSAm showed no significant association with ABMR (P=0.28). This study suggests no significant association between DSAm and biopsy-proven clinical ABMR. Further prospective research is needed to determine whether assessing DSAm could enhance existing immunological risk assessment methods for monitoring KTRs, particularly in non-sensitized KTRs.